MES-4: an autosome-associated histone methyltransferase that participates in silencing the X chromosomes in theC. elegansgerm line - Laurel B. Bender; Jinkyo Suh; Coleen R. Carroll; Youyi Fong; Ian M. Fingerman; Scott Briggs; Ru Cao; Yi Zhang; V Reinke; Susan Strome (2006)
Germ cell development in C. elegans requires that the X chromosomes be globally silenced during mitosis and early meiosis. We previously found that the nuclear proteins MES-2, MES-3, MES-4 and MES-6 regulate the different chromatin states of autosomes versus X chromosomes and are required for germline viability. Strikingly, the SET-domain protein MES-4 is concentrated on autosomes and excluded from the X chromosomes. Here, we show that MES-4 has histone H3 methyltransferase (HMT) activity in vitro, and is required for histone H3K36 dimethylation in mitotic and early meiotic germline nuclei and early embryos. MES-4 appears unlinked to transcription elongation, thus distinguishing it from other known H3K36 HMTs. Based on microarray analysis, loss of MES-4 leads to derepression of X-linked genes in the germ line. We discuss how an autosomally associated HMT may participate in silencing genes on the X chromosome, in coordination with the direct silencing effects of the other MES proteins.